2008
DOI: 10.1159/000135675
|View full text |Cite
|
Sign up to set email alerts
|

IFN-Inducible Protein 10 (CXCL10) Regulates Tubular Cell Proliferation in Renal Ischemia-Reperfusion Injury

Abstract: Although renal tubular cell proliferation after acute tubular necrosis is an important and essential response in the recovery of renal dysfunction in acute renal failure, the precise factors and mechanisms of tubular cell regeneration remain unclear. Here, we describe our studies using a neutralizing antibody (Ab) against interferon-inducible protein of 10 kDa (IP-10; CXCL10) that indicate a role for CXCL10 in tubular cell proliferation after renal ischemia-reperfusion injury. Tissue necrosis and interstitial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 63 publications
2
9
0
1
Order By: Relevance
“…Therefore, renal disease could be affected by the stimulation of TLRs in leucocytes or renal cells. Zhai et al reported that TLR4-IRF3 activation triggers CXCL10 expression in ischemia reperfusion injury (IRI) mouse liver [22], and Furuichi et al found that CXCL10 was expressed in the kidney after IRI [34]. Thus, we investigated the expression of TLR4 and phosphorylated (activated) IRF3 in both Mxi1 −/− and Mxi1 +/+ mice.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, renal disease could be affected by the stimulation of TLRs in leucocytes or renal cells. Zhai et al reported that TLR4-IRF3 activation triggers CXCL10 expression in ischemia reperfusion injury (IRI) mouse liver [22], and Furuichi et al found that CXCL10 was expressed in the kidney after IRI [34]. Thus, we investigated the expression of TLR4 and phosphorylated (activated) IRF3 in both Mxi1 −/− and Mxi1 +/+ mice.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to Cxcl1/KC, Cxcl2/MIP-2α has also been shown to stimulate proliferation of epithelial cells (43). Conversely, Furuichi et al (44) showed that the induction of Cxcl10/IP-10 in ischemic kidney inhibits tubular cell proliferation. This controversy can be explained by the presence or absence of the ELR motif in CXC chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…On this topic we reported that IP-10 had an inhibitory effect on tubular cell proliferation in vivo and in vitro. The interstitial infiltrated F4/80-positive cells were main source of IP-10 [39]. Further studies are needed to investigate whether regeneration from tubular necrosis is a very important part of recovery of the injured kidney.…”
Section: Regenerationmentioning
confidence: 99%